Pathways of care for HIV infected children in Beira, Mozambique: pre-post intervention study to assess impact of task shifting - Claudia Marotta; Carlo Giaquinto; Francesco Di Gennaro; Kajal D. Chhaganlal; Annalisa Saracino; Jorge Moiane; Guido Maringhini; Damiano Pizzol; Giovanni Putoto; Laura Monno; Alessandra Casuccio; Francesco Vitale; et al. (BMC, 2018)
Abstract Background In 2013, Mozambique implemented task-shifting (TS) from clinical officers to maternal and child nurses to improve care for HIV positive children < 5 years old. A retrospective, pre-post intervention study was designed to evaluate effectiveness of a new pathway of care in a sample of Beira District Local Health Facilities (LHFs), the primary, local, community healthcare services. Methods The study was conducted by accessing registries of At Risk Children Clinics (ARCCs) and HIV Health Services. Two time periods, pre- and post-intervention, were compared using a set of endpoints. Variables distribution was explored using descriptive statistics. T-student, Mann Whitney and Chi-square tests were used for comparisons. Results Overall, 588 HIV infected children (F = 51.4%) were recruited, 330 belonging to the post intervention period. The mean time from referral to ARCC until initiation of ART decreased from 2.3 (± 4.4) to 1.1 (± 5.0) months after the intervention implementation (p-value: 0.000). A significant increase of Isoniazid prophylaxis (O.R.: 2.69; 95%CI: 1.7-4.15) and a decrease of both regular nutritional assessment (O.R. = 0.45; 95%CI: 0.31-0.64) and CD4 count at the beginning of ART (O.R. = 0.46; 95%CI: 0.32-0.65) were documented after the intervention. Conclusions Despite several limitations and controversial results on nutrition assessment and CD4 count at the initiation of ART reported after the intervention, it could be assumed that TS alone may play a role in the improvement of the global effectiveness of care for HIV infected children only if integrated into a wider range of public health measures.